2023
DOI: 10.4103/jdmimsu.jdmimsu_466_21
|View full text |Cite
|
Sign up to set email alerts
|

Role of GATA-3 Expression in Urothelial Carcinoma and ITS Correlation with p53 by Immunohistochemistry

Kalpana Chandra,
Anuja Mishra,
Sanjeet Kumar Singh
et al.

Abstract: Background and Objectives: Urothelial carcinomas are known for divergent differentiation, which often poses diagnostic challenges. The use of immunohistochemistry (IHC) markers helps in differentiating these entities and provides insight into tumor pathogenesis. This study is done with the objective of evaluating significant clinicopathological and histomorphological features of urothelial carcinoma and correlating with GATA-3 and P53 staining. Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…In this study, necrosis was observed in 24.5% of patients with UC and an equal number of these patients showed negative and strong positive GATA3 expression (n=5 for both). In a study conducted by Chandra et al [15], they documented a correlation between the presence of necrosis and GATA3 expression (p=0). Additionally, Agarwal et al [8] found a significant statistical association between weak or absent GATA3 expression and the presence of necrosis (p = 0.019), which contrasted with the findings of this study.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, necrosis was observed in 24.5% of patients with UC and an equal number of these patients showed negative and strong positive GATA3 expression (n=5 for both). In a study conducted by Chandra et al [15], they documented a correlation between the presence of necrosis and GATA3 expression (p=0). Additionally, Agarwal et al [8] found a significant statistical association between weak or absent GATA3 expression and the presence of necrosis (p = 0.019), which contrasted with the findings of this study.…”
Section: Discussionmentioning
confidence: 94%